The role of the family in shaping the system of values in preschool children‏ - Pękala, Anna (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2015)
A child’s environment, with its family in the first place, creates the best space to lead a properly directed educational progress. The family as a fundamental social unit is characterized by the greatest continuity and regularity. It should provide the best conditionsfor child’s development. There are several important issues in this educational process which are carried out by the family. It is not only the emotional attitude but also the means of its expression as well as the ability to meet the child’s needs. A family is a place where a child is being prepared for life, where it learns to tolerate various difficulties and failures and where it learns to take responsibility for its duties. The shaping of moral attitudes is an extremely important issue in the process of children's education. Developing and shaping an appropriate and fixed hierarchy of values is a necessary factor for conscious living and making responsible decisions, making choices and manifesting certain behaviour. The system of values passed in the family consists of not only certain behaviour, home atmosphere and lifestyle but also expectations of shaping fixed features of character. These patterns are passed by means of opinions, views, knowledge and accepted standards.
Keywords: family; education; child; moral attitudes